TRADISI SAMBATAN DAN NYADRAN DI DUSUN SURUHAN - Anam, Choerul (Sabda: Jurnal Kajian Kebudayaan, 2017)
The people of Suruhan, Jubelan, Sumowono, Semarang has two important traditions, Sambatan and Nyadran which have been done since Kyai Bumi and Nyai Bumi (folktale figures) era. The word Sambatan derives from two words Sambet and Batan meaning helping someone who is doing a particular activity (traditional ceremony) including building a house. Meanwhile, Nyadran is a way of thanking God, Allah Subhanahu wa ta’ala, for the blessing given to all people of Suruhan and a way of praying fot the dead. There are two types of Nyadran, one which is held in the house of the dead at night of his/her death, and the other one in the cemetery on the next morning after his/her death. In Suruhan, Nyadran is always done on Friday before fasting month (Ramadhan). In this study, Semiotics theory is used to reveal the meaning of these two traditions by interviewing people of Suruhan who understand well about these traditions.